Clinical use of tigecycline may contribute to the widespread dissemination of carbapenem-resistant hypervirulent Klebsiella pneumoniae strains - Miaomiao Xie; Lianwei Ye; Kaichao Chen; Qi Xu; Chen Yang; Xiangnan Chen; Edward Wai-Chi Chan; Fuyong Li; Sheng Chen (Emerging Microbes and Infections, 2024)
The emergence of carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKP) poses grave threats to human health. These strains increased dramatically in clinical settings in China in the past few years but not in other parts of the world. Four isogenic K. pneumoniae strains, including classical K. pneumoniae, carbapenem-resistant K. pneumoniae (CRKP), hypervirulent K. pneumoniae (hvKP) and CR-hvKP, were created and subjected to phenotypic characterization, competition assays, mouse sepsis model and rat colonization tests to investigate the mechanisms underlying the widespread nature of CR-hvKP in China. Acquisition of virulence plasmid led to reduced fitness and abolishment of colonization in the gastrointestinal tract, which may explain why hvKP is not clinically prevalent after its emergence for a long time. However, tigecycline treatment facilitated the colonization of hvKP and CR-hvKP and reduced the population of Lactobacillus spp. in animal gut microbiome. Feeding with Lactobacillus spp. could significantly reduce the colonization of hvKP and CR-hvKP in the animal gastrointestinal tract. Our data implied that the clinical use of tigecycline to treat carbapenem-resistant K. pneumoniae infections facilitated the high spread of CR-hvKP in clinical settings in China and demonstrated that Lactobacillus spp. was a potential candidate for anticolonization strategy against CR-hvKP.